Evaluation of three-dimensional poly (lactic-co-glycolic acid), atelocollagen and fibrin scaffolds for intervertebral disc tissue engineering - Mohd Yusof bin Mohamad (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2017)
Tissue engineering and regenerative medicine (TERM) offers an alternative approach for the treatment of intervertebral disc (IVD) degeneration. One of the important TERM principles is the application of biomaterial scaffolds. Poly(lactic-co-glycolic acid) (PLGA) is a US Food and Drug Administration (FDA) approved synthetic copolymer for clinical use. However, for TERM application, PLGA needs to be improved. Natural polymers, for example atelocollagen and fibrin can be used to enhance the PLGA properties. The combination of PLGA with atelocollagen and fibrin for IVD regeneration has not been explored yet. The aim of the present study is to evaluate firstly the monolayer culture of IVD cells, secondly the PLGA-based scaffolds namely PLGA alone, PLGA with atelocollagen (PA), PLGA with fibrin (PF) and PLGA with the combination of both atelocollagen and fibrin (PAF), thirdly the in vitro 3D constructs engineered from PLGA-based scaffold seeded with the annulus fibrosus (AF) cells and fourthly the in vivo constructs implanted subcutaneously on the athymic nude mice model. Important Islamic principles in relation with the IVD regeneration were also discussed as the fifth objective. Growth kinetics analysis and cellular proliferation assay were performed on the monolayer cells culture and in vitro constructs at day 4, 7, 14 and 21, respectively. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were used to evaluate cell morphology both in monolayer and the in vitro 3D culture. The fabricated PLGA- based scaffolds were characterized in terms of chemical bonding, porosity, water uptake, thermal, mechanical, degradation, pH level and compression modulus. Other evaluation parameters included histology, immunohistochemistry, gene expression, sulphated glycosaminoglycan (sGAG) and DNA quantification analysis. All constructs were evaluated at 1, 2 and 3 weeks in vitro and, at 4 weeks in vivo. The presence of autophagasome in AF cells was detected in all passages. Comparable morphology of cellular attachment on in vitro 3D constructs was observed. Passage 1 of AF cells showed better cellular profile and extracellular matrix production compared to all other passages thus chosen to be seeded onto PLGA-based scaffolds and form constructs. The PA scaffolds showed better swelling ratios, thermal stability, mechanical strength, degradation properties and ability to reduce the pH effect. As for in vitro 3D constructs, PAF exhibited higher cellular proliferation and depicted better histological staining than the other groups. Positive accumulation of collagen type I and type II with higher level of sGAG were also observed in PAF constructs. Comparable mRNA expression of condrogenic markers were detected in all monolayer, in vitro 3D constructs and in vivo samples. In line with in vitro 3D constructs, in vivo constructs especially PAF group showed notable distribution of cells, accumulation of sGAG, and proteoglycan with positive immunoreactivity of collagen type I and type II. In conclusion, the incorporation of atelocollagen, fibrin and both combination significantly improved PLGA scaffold properties in vitro and in vivo. The desk-based study on Islamic perspective indicated that TERM technology does not violate any principles of Islam. More works on IVD regeneration are needed to uncover its full potential. This laboratory grown IVD may serve as an alternative over conventional treatments in future clinical application.